The roles of innovation in competition law analysis - Nihoul, Paul, 1963-; Cleynenbreugel, Pieter van (ASCOLA competition law, 2018)
Rapid technological innovations have challenged the conventional application of antitrust and competition law across the globe. Acknowledging these challenges, this original work analyses the roles of innovation in competition law analysis and reflects on how competition and antitrust law can be refined and tailored to innovation. With chapters from well-established and up-and-coming competition law and economics scholars - from the Academic Society for Competition Law (ASCOLA) - this book reflects on the role innovation has played, and can continue to play, within competition and antitrust law. In addition to uncovering innovation concerns within their analysis, the authors also make important contributions to academic and policy debates on the relationship between these areas of law and other instruments of innovation regulation, such as data protection regulation, intellectual property law, the regulation of big data, platforms and artificial intelligence. Academics in competition and intellectual property law, economics and political science working on data protection or innovation more generally will find this book a useful insight into future challenges for constructing meaningful and effective laws within the area of innovation. Policymakers and practising lawyers will also find the example cases useful, especially for refining and restructuring perception about innovation in competition law.